2013
DOI: 10.1038/srep01988
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Condensation on Oil-Infused Heterogeneous Surfaces for Enhanced Heat Transfer

Abstract: Enhancing condensation heat transfer is important for broad applications from power generation to water harvesting systems. Significant efforts have focused on easy removal of the condensate, yet the other desired properties of low contact angles and high nucleation densities for high heat transfer performance have been typically neglected. In this work, we demonstrate immersion condensation on oil-infused micro and nanostructured surfaces with heterogeneous coatings, where water droplets nucleate immersed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
219
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(230 citation statements)
references
References 40 publications
1
219
1
2
Order By: Relevance
“…g wo /g wa < 1), E III /E 1 can be greater than one so that nucleation in the air environment may be more preferred compared to nucleation within a liquid, contrary to the hypothesis of Xiao et al 25 At the same time, even if g wo /g wa > 1, nucleation within the liquid may be enhanced if the contact angle terms are such that eqn (2) is satised. j 1 and j 2 are related to the contact angles of condensate in air (q ws(a) ) and oil (q ws(o) ), respectively, and lie in the limits of 0 # {j 1 , j 2 } # 4.…”
Section: Nucleation States and Energetic Barriersmentioning
confidence: 66%
See 1 more Smart Citation
“…g wo /g wa < 1), E III /E 1 can be greater than one so that nucleation in the air environment may be more preferred compared to nucleation within a liquid, contrary to the hypothesis of Xiao et al 25 At the same time, even if g wo /g wa > 1, nucleation within the liquid may be enhanced if the contact angle terms are such that eqn (2) is satised. j 1 and j 2 are related to the contact angles of condensate in air (q ws(a) ) and oil (q ws(o) ), respectively, and lie in the limits of 0 # {j 1 , j 2 } # 4.…”
Section: Nucleation States and Energetic Barriersmentioning
confidence: 66%
“…1a-State III), or at the oil-air interface (heterogeneous nucleation on oil, Fig. 25 However, these observations could also be attributed to the nucleation at the oil-air interface (State IV), as it may also be energetically favourable compared to State I. Nucleation of water droplets on bulk oil surfaces is well known, 26,40 and very large nucleation rates have also been observed on bulk oils. In a recent work, it has been suggested that enhancement in nucleation rate occurs on LIS compared to superhydrophobic surfaces because the presence of 'high surface energy sites' on the submerged solid surfaces results in signicantly lower energy barrier in State III compared to State I.…”
Section: Nucleation States and Energetic Barriersmentioning
confidence: 97%
“…Though droplet coalescence will eventually occur due to film drainage, the time required for film rupture is several hours for moderate-viscosity [∼100 centistokes (cSt)] oils and is 1-3 orders of magnitude longer compared with droplets submerged in an oil bath (40,(42)(43)(44). These findings should refine the understanding of using oil-infused substrates for processes involving droplet-droplet interactions, such as condensation (9,10) and fog harvesting (12).…”
mentioning
confidence: 93%
“…In contrast to dry, superomniphobic surfaces (6), lubricant-infused surfaces demonstrate stable liquid repellency at extreme pressures and temperatures (5,7), are self-healing to mechanical damage (5), and their wettability and optical properties can be tuned (7,8). A wide variety of applications are being explored for lubricant-infused surfaces, such as enhancing condensation heat transfer (9,10), self-cleaning (11), fog harvesting (12), and omniphobic textiles (13), or minimizing ice nucleation (14,15), ice adhesion (16,17), and biofouling (18). Though previous studies have characterized the dynamics and possible wetting states of isolated droplets on lubricant-infused surfaces (5,(19)(20)(21)(22), the interactive behavior of multiple droplets has not been reported.…”
mentioning
confidence: 99%
“…Understanding the mechanisms governing water condensation on surfaces is crucial to a wide range of applications that have a significant societal and environmental impact, such as energy conversion [1][2][3], water harvesting [4,5], water desalination [6], thermal management systems [7][8][9][10][11] and environmental control [12].…”
Section: Introductionmentioning
confidence: 99%